Las franquicias como estrategia de crecimiento para el mercado de la empresa "Los Famosos Motes de la Biloxi" - Álvarez Valero, Fernando José (2007)
This alternative is represented in Excess whose strategy is developed by the largest global food chains, allowing them not only to conquer local markets but also get to position themselves in the world. This thesis proposes the growth of the company object of this study by the franchise, which is to grant to third parties the rights to operate the company's brand positioning usufruct thereof and its know how, since then the company benefits will receive royalties, minimum investment representative presence in the market, reducing costs through economies of scale, orderly growth that is not to the detriment of the quality of products etc.